Statutory minimum wages in the EU 2018: first findings - Fric, Karel; Gaughan, Sinead (Dublin, 2018)
"In 2018, 22 out of the 28 EU Member States apply a generally binding statutory minimum wage. In Cyprus, a statutory minimum wage exists but is limited to specific occupations. In the remaining five EU Member States (Austria, Denmark, Finland, Italy and Sweden), while there is no statutory minimum wage, the minimum wage level is de facto set in (sectoral) collective agreements. It is important to note that the coverage of these agreements varies between countries and, as some employees are not covered, they may not be entitled to any minimum wage. According to an article by Garnero et al (2015), the combination of sectoral minima and high collective bargaining coverage can be regarded as the functional equivalent of a binding statutory minimum wage, at least for earnings inequalities. The focus of this article is on those countries having a generally applicable statutory minimum wage. There is a huge variation in the statutory minimum wage rates valid at 1 January 2018 across EU Member States."